OPTIMALISASI PERAN OBSERVERDALAM LESSON STUDY UNTUK MENINGKATKAN KOMPETENSI DOSEN - Budiarta, I Komang (Jurnal Santiaji Pendidikan (JSP), 2019)
A lecturer should do an ‘extra efforts’ to make the teaching learning process run smoothly. However, during the process, there is a fallibility which might not be directly observed by the lecturer. The lecturer, therefore, needs to carry out an evaluation of his/ her teaching. It can be done is through applying Lesson Study which consists of plan, do and see and involving observers to optimize the process. This research was limited on answering the research problems: what are the observers’ roles in lesson study to improve the competency of the lecturers? and what are the mutual feedback of the observers in conducting lesson study? The design of this study was descriptive and qualitative research. The required data were collected by using active-participatory observation by observing 3 observers and 5 model lecturers. In addition, the researcher also did post-interview. Based on two cycles of lesson study, the researcher found that the observers had significant roles to improve their competency. Moreover, the findings showed that they got mutual feedback to improve their competency and classroom management which is discipline, active, interactive, enjoyable, and motivating to make an active learning. This proves that lesson study is worth to be applied in developing the competency of the lecturers in faculty of teacher training and education.